A preliminary investigation into the levels of readability of comprehension passages set in the Senior Certificate examinations of the four Provincial Education Departments - Wanliss, P.(Peter) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Ed.) -- University of Stellenbosch, 1988.